Cost-Effective Synthesis of Bule-OH: An Alternative to Bulevirtide for Hepatitis B and D Research - Zhu, Hongxiang; Hua, Haoju; Dong, Yuanzhen; Xu, Hongjiang; Feng, Jun (Pharmaceutical Fronts, 2025)
Bulevirtide is a hepatitis B virus/hepatitis D virus (HDV) entry inhibitor that has been commercially available in Europe. It is manufactured via solid-phase synthesis of 47 amino acids with N-terminal myristoylation on MBHA resin. This production method presents significant environmental and economic challenges that limit the accessibility for patients. This study aims to develop a more sustainable and cost-efficient alternative through the rational design of Bule-OH, a Bulevirtide analogue featuring C-terminal carboxyl modification, rather than Bulevirtide's C-terminal amide. In this work, Bule-OH is successfully synthesized by combining fermentation expression with chemical modification techniques to reduce production costs. Bule-OH has a carboxylic acid group at the C-terminus, whereas Bulevirtide has an amide. We compared the pharmacological profiles of Bule-OH and Bulevirtide by determining their functional performance, including activity and enzymatic stability; and biophysical properties, including stability and self-association assays, followed by their pharmacokinetic evaluation in hNTCP (human sodium taurocholate cotransporting polypeptide) mice model of HDV infection. The results showed that the pharmacokinetic characteristics of Bule-OH and Bulevirtide in the target organ, the liver, were similar, whereas Bule-OH had a stronger liver targeting ability. These findings suggest that Bule-OH has the potential to be an economical and efficient alternative to Bulevirtide.
Keywords: Bulevirtide; Bule-OH; production costs; pharmacokinetic